(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2024)
The use of high-quality Urochloa decumbens seeds is an essential factor for the establishment of pastures, and osmopriming under stress conditions may improve seed performance. This study was conducted at the Universidade Federal de Viçosa in a completely randomized design and aimed to evaluate the effects of osmopriming and its relationship with physical and physiological attributes of U. decumbens seeds subjected to water deficit. Seeds from ten lots were primed in H2O (0 MPa) and PEG (−0.8 MPa), KNO3 (0.2%), and SNP (0.10 mmol L−1) solutions for 24 hours. Unprimed seeds were used as control. The seeds were evaluated in two trials after osmopriming. Trial I consisted of the X-ray test to evaluate physical attributes and germination and vigor tests. In Trial II, the seeds were placed to germinate under favorable (0 MPa) and water deficit conditions (−0.2 MPa) to evaluate physiological attributes. In general, osmopriming of U. decumbens seeds assisted in increasing physical attributes such as area, gray scale, perimeter, and tissue density. Osmopriming does not contribute to the best physiological performance of U. decumbens seeds under ideal germination conditions (0 MPa). However, osmopriming with SNP (0.10 mmol L−1) and PEG (−0.8 MPa) for 24 hours contributes to the better physiological performance of seeds under water deficit.